Individual Differences in Working Memory and the N2pc - Couperus, Jane W.; Lydic, Kirsten O.; Hollis, Juniper E.; Roy, Jessica L.; Lowe, Amy R.; Bukach, Cindy M.; Reed, Catherine L. (Frontiers in Human Neuroscience, 2021)
The lateralized ERP N2pc component has been shown to be an effective marker of attentional object selection when elicited in a visual search task, specifically reflecting the selection of a target item among distractors (Eimer, Kiss, & Nicholas, 2011). Moreover, when targets are known in advance, the visual search process is guided by representations of target features held in working memory at the time of search, thus guiding attention to objects with target-matching features (Grubert & Eimer, 2016). Previous studies have shown that manipulating working memory availability via concurrent tasks or within task manipulations influences visual search performance and the N2pc. Other studies have indicated that visual (non-spatial) versus spatial working memory manipulations have differential contributions to visual search. To investigate whether visual and spatial working memory availability contribute differentially to visual search, we assess participants’ visual and spatial working memory ability independent of the visual search task to determine whether such individual differences in working memory availability affect task performance and the N2pc. Participants (n=205) completed a visual search task to elicit the N2pc and separate visual working memory (VWM) and spatial working memory (SPWM) assessments. Greater SPWM, but not VWM, ability is correlated with and predicts higher visual search accuracy and greater N2pc amplitudes. Neither VWM nor SPWM was related to N2pc latency. These results provide additional support to prior behavioral and neural visual search findings that spatial WM availability, whether as an ability of the participant’s processing system or based on task demands, plays an important role in efficient visual search.